Biomaterials: The Bioinspired Facile Method to Efficiently Generate Diverse Proteinosomes with pH Switchable Permeability (Adv. Mater. Interfaces 14/2020). Issue 14 (27th July 2020) - Qin, Jianghui; Wei, Shaoyin; Xu, Hongyan; Wang, Liwen; Hao, Pengyan; Peng, Bo; Zhang, Yagang; Shi, Pengzhong; Zan, Xingjie
Abstract : Inspired by polyphenol chemistry, a facile and universal method is presented to fabricate the diverse proteinosomes, with independence on the amino acid sequence, isoelectric points, molecular weight (Mw), wettability, and functional domains of applied proteins. The materials employed here are green and cost‐effective, the method developed here is efficient and easily operated without any expensive equipments. In addition, the permeability of the proteinosomes can be reversibly switched on/off in 100% by environmental pH. More details can be found in article number 2000329 by Pengzhong Shi, Xingjie Zan, and co‐workers.